2022
DOI: 10.3390/healthcare10112234
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Work-Life Balance on the Emotional Exhaustion and Well-Being of College Teachers in China

Abstract: UN Sustainable Development Goal 3 states that “Ensuring healthy lives and promoting well-being at all ages is essential to sustainable development.” The sustainable well-being of college teachers deserves attention. Currently, college teachers in China are facing enormous challenges and pressures, which may increase their emotional exhaustion (EE) and hinder the sustainable development of their well-being (WB). Therefore, this study examined Chinese college teachers’ well-being in relation to their work-life b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 98 publications
0
7
0
Order By: Relevance
“…For instance, as the usual primary caregivers in their families, women teachers may face unique challenges related to their work-life balance. Adding these challenges to social expectations and gender roles might increase the stress that women teachers must deal with, making them potential candidates for burnout (Wei & Ye, 2022). Alternatively, Zhang et al (2022) suggested that, compared with men teachers, women teachers may look more favorably on the school's culture and manage their emotions more proactively to maintain their relationships in the school, work collaboratively with others and actively seek consensus in the school.…”
Section: Gender Related Teacher Burnoutmentioning
confidence: 99%
“…For instance, as the usual primary caregivers in their families, women teachers may face unique challenges related to their work-life balance. Adding these challenges to social expectations and gender roles might increase the stress that women teachers must deal with, making them potential candidates for burnout (Wei & Ye, 2022). Alternatively, Zhang et al (2022) suggested that, compared with men teachers, women teachers may look more favorably on the school's culture and manage their emotions more proactively to maintain their relationships in the school, work collaboratively with others and actively seek consensus in the school.…”
Section: Gender Related Teacher Burnoutmentioning
confidence: 99%
“…A study conducted in China on the impacts of work-life balance on the emotional exhaustion and well-being of college teachers (Wei & Ye, 2022). An online survey was conducted.…”
Section: Sarah Et Al (mentioning
confidence: 99%
“…Subjective well-being (SWB) is a key concept in the realm of psychology; an individual's level of SWB plays an important role in measuring mental health, academic performance [16], health behavior, and social adjustment [17].…”
Section: The Impact Of Covid-19 On University Students' Mental Health...mentioning
confidence: 99%